An Integrated Model to Enhance the Transportation Methods in Malaysia: Review Paper - Ali, A. J. Adham; Khaled Abdul Rahman, Jomaa; Alsibai, Mohammed Hayyan (AENSI Publisher, 2014)
In this study, we plan to construct a Simulation Model (SM) in corporate with the Road Network Design Method (RNDM), Genetic Algorithm system (GAs), and Optimization method. In order to elicit a general diagnosis for the traffic congestion problem in the main urban areas in Malaysia, and to find out the optimal solutions for transportation system problems in Malaysia. The problems of the transportation system in Malaysia are generally unsatisfactory to many of the customers due to be inability to connect different place. The country requires a better transportation system that could provide multi options to customers travel among the many places that might minimize the traffic congestion in the main urban areas. The results of this study will be reported and used to suggest and apply optimal transportation policies with the aim of providing useful insights on critical issues about the impact of such policies, and to help as a guide for the Malaysian decision makers to elaborate the optimal transportation policies.